Case of concurrence of bullous pemphigoid and Norwegian scabies. (29th January 2023) - wang, Xuesong; Liu, Yongxia; Li, Jianke; Bao, Fangfang; Chen, Mingfei
Abstract: Bullous pemphigoid (BP) with scabies is a condition rarely encountered in clinical practice, and when it is encountered, it is often due to the use of immunosuppressants. This paper is a report on a patient with BP and scabies, who developed scabs after taking dexamethasone. It should be noted that BP antibody is necessary, which can distinguish BP with scabies and bullous scabies, and the treatment options for the two diseases are different.